The regularity of Euclidean Lipschitz boundaries with prescribed mean curvature in three-dimensional contact sub-Riemannian manifolds. (May 2016) - Galli, Matteo
Abstract: In this paper we consider a set E ⊂ Ω with prescribed mean curvature f ∈ C ( Ω ) and Euclidean Lipschitz boundary ∂ E = Σ inside a three-dimensional contact sub-Riemannian manifold M . We prove that if Σ is locally a regular intrinsic graph, the characteristic curves are of class C 2 . The result is shape and improves the ones contained in Capogna et al. (2009) and Galli and Ritoré (2015).